Genetic variation in PLEKHG1 is associated with white matter hyperintensities (n = 11, 226). (19th February 2019) - Traylor, Matthew; Tozer, Daniel J.; Croall, Iain D.; Lisiecka Ford, Danuta M.; Olorunda, Abiodun Olubunmi; Boncoraglio, Giorgio; Dichgans, Martin; Lemmens, Robin; Rosand, Jonathan; Rost, Natalia S.; Rothwell, Peter M.; Sudlow, Cathie L.M.; et al.
Abstract : Objective: To identify novel genetic associations with white matter hyperintensities (WMH). Methods: We performed a genome-wide association meta-analysis of WMH volumes in 11, 226 individuals, including 8, 429 population-based individuals from UK Biobank and 2, 797 stroke patients. Replication of novel loci was performed in an independent dataset of 1, 202 individuals. In all studies, WMH were quantified using validated automated or semi-automated methods. Imputation was to either the Haplotype Reference Consortium or 1, 000 Genomes Phase 3 panels. Results: We identified a locus at genome-wide significance in an intron of PLEKHG1 (rs275350, β [SE] = 0.071 [0.013]; p = 1.6 × 10 −8 ), a Rho guanine nucleotide exchange factor that is involved in reorientation of cells in the vascular endothelium. This association was validated in an independent sample (overall p value, 2.4 × 10 −9 ). The same single nucleotide polymorphism was associated with all ischemic stroke (odds ratio [OR] [95% confidence interval (CI)] 1.07 [1.03–1.12], p = 0.00051), most strongly with the small vessel subtype (OR [95% CI] 1.09 [1.00–1.19], p = 0.044). Previous associations at 17q25 and 2p16 reached genome-wide significance in this analysis (rs3744020; β [SE] = 0.106 [0.016]; p = 1.2 × 10 −11 and rs7596872; β [SE] = 0.143 [0.021]; p = 3.4 × 10 −12 ). All identified associations with WMH to date explained 1.16% of the trait variance in UK Biobank, equivalent to 6.4% of the narrow-sense heritability. Conclusions: Genetic variation in PLEKHG1 is associated with WMH and ischemic stroke, most strongly with the small vessel subtype, suggesting it acts by promoting small vessel arteriopathy.